2022
DOI: 10.1007/s10433-021-00678-8
|View full text |Cite
|
Sign up to set email alerts
|

Does personality shape the personal social networks of older Europeans?

Abstract: The aim of the study was to clarify whether personality traits predict the structure, function and quality of egocentric confidant networks in later life. Data were drawn from Waves 7 and 8 of the Survey of Health, Ageing and Retirement in Europe (SHARE) (N = 39,172). We regressed network size, contact frequency and network satisfaction on the Big-5 personality traits, using a single path analysis structure, controlling for country, sociodemographic background and health status. The findings showed that the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…There is evidence that different personality traits predict social isolation. For example, Iveniuk (2019) [ 26 ] found that extraverted and agreeable people had larger and stronger social network ties than their counterparts; however, other personality characteristics (i.e., conscientiousness) can be positive in relation to social network outcomes [ 27 ].…”
Section: Antecedents Of Social Isolationmentioning
confidence: 99%
“…There is evidence that different personality traits predict social isolation. For example, Iveniuk (2019) [ 26 ] found that extraverted and agreeable people had larger and stronger social network ties than their counterparts; however, other personality characteristics (i.e., conscientiousness) can be positive in relation to social network outcomes [ 27 ].…”
Section: Antecedents Of Social Isolationmentioning
confidence: 99%